Genetic polymorphism of miR‐146a is associated with gastric cancer risk: a meta‐analysis. (23rd July 2015) - Sun, Y.; Li, M.
Abstract : Several studies have investigated the associations between miR‐146a rs2910164 and gastric cancer (GC) risk, but results have been inconclusive. To derive a more precise estimation of the relationship, a meta‐analysis was performed. PubMed and China National Knowledge Infrastructure searches were carried out for relevant studies published before July 2014. Meta‐analysis was performed with thestata, version 11.0. A total of seven case–control studies, including 3283 cases and 4535 controls, were selected. A significant association was found between rs2910164 and GC risk under all genetic models (CC vs. GG, OR = 0.76, 95% CI = 0.66–0.87; CC vs. GC+GG, OR = 0.84, 95% CI = 0.71–0.99; CC+GC vs. GG, OR = 0.82, 95% CI = 0.73–0.91) for the total data. In the subgroup analysis by ethnicity, statistically significant association was found in Asian. This meta‐analysis suggested that the miR‐146a rs2910164 was a risk factor for developing GC.